Wisata â€œManyamabrayaâ€: Paket Wisata â€œAjeg Baliâ€ Berbasis Local Genius - Dewi, Komang Trisna (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
This research is a qualitative research that aims to describe "manyamabraya" tourism based on local genius in the Mengali Traditional Village, Sawan-Buleleng District. The research data were collected using documentation, interview, and observation techniques with research instruments in the form of interview guides and observation sheets. The data collected was then analyzed descriptively qualitatively by following the interactive analysis method proposed by Miles and Huberman (1994). This study concludes that, (1) "Manyamabraya" tourism based on local genius in the Mengali Traditional Village is a tourism concept that provides the opportunity for tourists to be directly involved in the socio-cultural life of the community in the Mengali Traditional Village, (2) This tour was developed because of the natural and cultural potential which is very suitable to be developed into a cultural-based tourist destination, as well as the weakness of the community's economy has encouraged creative ideas to develop this "manyamabraya" tourism, (3) The "manyamabraya" tourism is managed directly independently by the community of the Mengali Indigenous Village, starting from providing accommodation, tourist activities, food, drinks and entertainment